Kajian Kekuatan Struktur Pondasi Mesin Induk Harbour Tug Boat - Kintan Muthia Yasmine Emily; Priyambodo Nur Ardi Nugroho; Boedi Herijono (Universitas Ivet, 2021)
The main engine has its own weight, and vibration also occurs so the heavier the load that the foundation holds. The foundation has an essential role as a retainer or support for the load, so it must be stronger to withstand the dynamic vibrations of the main engine. The installation of the foundation is made in such a way that the alignment of the engine shaft axis with the propeller shaft is guaranteed. The problem to be solved is how much load is received, whether the stress results still meet the class requirements, and the estimated age of the foundation. Using the calculation of applied mechanics, the load that will be received on the foundation and the main engine foundation construction planning can be known. To find out the results of the construction planning using the Finite Element Method. The analyzed structure is divided into smaller and simpler elements in a finite number by giving the value of the simulated structure boundary conditions. The analysis results show that the maximum stress value obtained is 267.1 MPa, while the allowable stress value is 300 N/mm2. So that the foundation can be declared to have met the requirements and is safe. For fatigue life analysis, the foundation age is 34,422 years, where the age has met the requirements